[Baby trafficking ; Lisa Macuja ; Squatters [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
An investigative report on NBI uncovering a West German syndicate allegedly operating baby trafficking. Interview with Lisa Macuja. Looks at squatting syndicate.